Analisis Isi Pesan Dakwah pada Novel Bumi Cinta Karya Habiburrahman El Shirazi - Hamidah Hamidah; Manalullaili Manalullaili; M Akbar (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2017)
In a literary work, the message of da'wah can always be packed interestingly by the author. Novel Bumi Cinta is one of the most popular Islamic novels ever published. This novel is written from Habiburrahman El Shirazy. The purpose of this research is to examine and explain the message of da'wah contained in the novel. In this thesis the authors use descriptive qualitative method, the data used is the description of the existing story on the dialogue and the paragraphs found in the novel. By using qualitative content analysis technique can get description of mass communication message content objectively, systematically, and relevant sociologically, description and analysis. In this thesis message da'wah in categorize into three parts, namely: aqidah message, message sharia, and morals messages. After the analysis and the various kinds there are many messages of da'wah contained in the novel, but of the three categories of message preaching is the most dominant of this novel is about the message aqidah, which this novel is intended to teach the readers how to defend the aqidah from temptation world.